The Enforcement Mechanism of the Comparison of Uganda and South Africa on the Right to a Clean and Healthy Environment. - Patrick Chuki (Uganda Christian University, 2025)
This is a comparative legal study on the enforcement of the right to a clean and healthy environment in Ugandan and South African law: that is the focus of this thesis. Given that both countries affirm this right in their respective constitutions under Article 39 of Uganda’s 1995 Constitution and Section 24 of South Africa’s 1996 Constitution the study focuses on why it has not been enforced uniformly. The research surveys the applicable international and regional legal instruments, takes a critical look at statutory frameworks, and scrutinizes the most prominent case law and recent policy developments in both jurisdictions. It is based on a doctrinal and comparative methodology drawing on secondary materials mainly, statutes, court decisions, academic writings and official reports. Results indicate that despite progressive statutory arrangements, enforcement of the environmental law is hampered by institutional redundancy, lack of resources, political meddling with the law and limited public participation. On the other hand, in South Africa judicial activism has been more pronounced, there are specialized enforcement agencies and compliance levels are high, although problems remain at the level of local government. The research suggests that effectiveness of the enforcement of environmental rights cannot be achieved just by providing a legal recognition, but it requires adequate enforcement mechanisms and institutional capacity, and involvement of the public. Recommendations include building enforcement institutions in Uganda, increasing public participation, and taking lessons learned from South Africa such as creation of an Environmental Enforcement Courts and Prosecutors. Influence: This research has implications for the operationalization of environmental justice and sustainable development in Africa and provides a heuristic tool for policy makers and legal practitioners.
Undergraduate Research